2018
DOI: 10.3390/f9120777
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical Environmental Factors Affecting the Distribution of Abies koreana on the Korean Peninsula

Abstract: A regional decline in the Korean fir (Abies koreana) has been observed since the 1980s in the subalpine region. To explain this decline, it is important to investigate the degree to which environmental factors have contributed to plant distributions on diverse spatial scales. We applied a hierarchical regression model to determine quantitatively the relationship between the abundance of Korean fir (seedlings) and diverse environmental factors across two different ecological scales. We measured Korean fir densi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…Our results suggest that QUMO, as an early invader of disturbed areas with the ability to quickly dominate stands (Suh and Lee 1998) in combination with warmingenhanced growth at its upper distributional limit, has potential to further reduce ABKO distribution (Park et al 2018). The only ABKO population profiting from warming temperatures is located at the peak of highest mountain of South Korea and thus lacks the option of migrating to higher elevation.…”
Section: Discussionmentioning
confidence: 81%
“…Our results suggest that QUMO, as an early invader of disturbed areas with the ability to quickly dominate stands (Suh and Lee 1998) in combination with warmingenhanced growth at its upper distributional limit, has potential to further reduce ABKO distribution (Park et al 2018). The only ABKO population profiting from warming temperatures is located at the peak of highest mountain of South Korea and thus lacks the option of migrating to higher elevation.…”
Section: Discussionmentioning
confidence: 81%
“…Furthermore, a recent study by Park et al. [ 51 ] showed that the major soil textures of A. koreana were loam (Mt. Jiri) and SiL (Mts.…”
Section: Resultsmentioning
confidence: 99%
“…Deogyu and Halla). In addition, SL and SiL are typically considered as the most suitable soil textures for Korean fir [ 13 , 51 , 52 ] since they possess excellent nutrient and water holding capacities. Moreover, it was found that two of our study sites on Mt.…”
Section: Resultsmentioning
confidence: 99%
“…The largest number of these trees are found on Mt. Halla, a volcanic mountain with the highest peak (~1950 m altitude above sea level) located in the center of the largest island in the Korean peninsula, Jeju Island [ 2 , 3 ]. The Korean fir tree was declared an endangered species ( , accessed on 1 February 2022) by the International Union of Conservation of Nature (IUCN) because of its continuous decline in numbers since the 1980s [ 4 ].…”
Section: Introductionmentioning
confidence: 99%